Association Between Birth Weight Z-Scores and Early Outcomes Following Truncus Arteriosus Repair - Stephenson, Joseph J.; Hook, Jessica E.; Beall, Jonathan; Delany, Dennis R.; Buckley, Jason R.; Chowdhury, Shahryar M.; Steurer, Martina A.; Kavarana, Minoo N.; Costello, John M. (Pediatric cardiology, 2023)
In infants undergoing truncus arteriosus (TA) repair, we sought to determine associations between fetal growth restrictions as measured by birth weight Z-score and early outcomes. We utilized the Pediatric Health Information System (PHIS) database to identify infants < 90 days old who underwent TA repair from 2004 to 2019. The primary exposure variable was birth weight Z-score, calculated based on gestational age at birth, gender, and birth weight. The primary outcome was postoperative hospital mortality. Secondary outcomes included major complications, prolonged postoperative length of hospital stay (LOS; > 30 days), and hospital readmission within 1 year. Generalized estimating equation (GEE) models were used to identify adjusted associations between birth weight Z-score, small for gestational age (SGA) status, and mortality and included were 1039 subjects. Median birth weight was 2960 g, gestational age at birth was 38 weeks, and birth weight Z-score was − 0.47. SGA was present in 21% of subjects. Hospital mortality occurred in 104 patients (10%). By multivariable analysis, lower birth weight Z-score was associated with higher hospital mortality [for each unit decrease in birth weight Z-score below − 1.0, adjusted OR 1.71 (95% CI 1.10–4.25)]. SGA status was associated with increased hospital mortality (adjusted OR 2.17; 95% CI 1.39–3.40). Birth weight Z-scores and SGA status were not significantly associated with occurrence of cardiac arrest, ECMO use, gastrostomy tube placement, tracheostomy, seizures, infection, prolonged postoperative LOS, or hospital readmission. In infants undergoing TA repair, lower birth weight Z-scores and SGA status were strongly associated with increased hospital mortality.